PROGRAM RECOGNITION LETTERS AND PRAYER WITH swish 2.0 - Budhi Tjahyo Prasetiyo; Cut Asiana Gemawaty, SKom, MMSI (Jurnal Sistem Informasi, 2001)
The introduction of computers to children can be started from 4-year-old child that isthe way to teach them how to use the correct computer and by providing interestingprograms that contain elements of education, or games.This program includes education for learning letters and prayers are allocated tochildren aged 4 years upwards.